50 years of social marketing: seeding solutions for the future. (21st April 2022) - Dietrich, Timo; Hurley, Erin; Kassirer, Jay; Rundle-Thiele, Sharyn; Palmatier, Robert W.; Merritt, Rowena; Weaven, Scott K.; Lee, Nancy
Abstract : Purpose: The purpose of this paper is synthesise social marketing literature over the past fifty years and deliver a set of guiding tenets to propel social marketing's agenda forward. Design/methodology/approach: Across three strands, this paper amalgamates theoretical and practitioner evidence from social marketing. This synthesis commences with a review, summary and critical discussion of five decades of social marketing research. Across Strands 2 and 3, the authors review 412 social marketing interventions reported across 10 evidence reviews and 238 case studies. Findings: This paper demonstrates social marketing's use of fundamental marketing principles and capability to achieve behaviour change outcomes. Social marketers have built frameworks and processes that non-profit organisations, government agencies and policymakers seeking to enact change can use. This paper delivers five tenets that summarise the findings of the three strands and delivers research priorities for the next 50 years of social marketing research to drive the field forward. Research limitations/implications: Drawing on five decades of learning, this paper proposes research priorities that can be applied to refine, recalibrate and future-proof social marketing's success in making the world a better place. Practical implications: This paper demonstrates the value of social marketing science and helps bridge gaps between theory and practice, and further strengthens social marketing's value proposition. This paper provides confidence that money invested in social marketing programs is well spent. Originality/value: This paper delivers a forward-looking perspective and provides social marketing academics and practitioners with confidence that it can assist in overcoming society's most pressing issues. The paper encompasses key social marketing literature since it was founded 50 years ago. Five tenets will guide social marketing forward: evidencing marketing principles, operationalisation of processes, principles and activities, implementing systems thinking, creating and testing marketing theory and guiding a new social marketing era.